Navigating The Interplay Between Sustainable Leadership, Relational Capital, And Academic Performance In Higher Education - Achmad Sani Supriyanto; Siswanto; Eko Suprayitno; Vivin Maharani Ekowati; Fuadah Binti Johari; Mohammad Taqiuddin; Muhtadi Ridwan; Nur Ali; Lempang Hasibuan (The International Journal of Religion (IJOR), 2024)
Non-Indexed Publication